Trends in Adherence to Recommended Cancer Screening: The US Population and Working Cancer Survivors - Clarke, Tainya C.; Soler-Vilá, Hosanna; Fleming, Lora E.; Christ, Sharon L.; Lee, David J.; Arheart, Kristopher L. (Frontiers in Oncology, 2012)
Introduction: Over the past decade the United States has seen a decrease in advanced cancer diagnoses. There has also been an increase in the number of cancer survivors returning to work. Cancer screening behaviors among survivors may play an important role in their return-to-work process. Adherence to a post-treatment cancer screening protocol increases early detection of secondary tumors and reduces potentially limiting side-effects. We compared screening trends among all cancer survivors, working survivors, and the general population over the last decade. Methods: Trends in adherence to recommended screening were analyzed by site-specific cancer. We used the Healthy People goals as a measure of desired adherence. We selected participants 18+ years from 1997 to 2010 National Health Interview Survey (NHIS) for years where detailed cancer screening information was available. Using the recommendations of the American Cancer Society as a guide, we assessed adherence to cancer screening across the decade. There were 174,393 participants. Analyses included 7,528 working cancer survivors representing 3.8 million US workers, and 119,374 adults representing more than 100 million working Americans with no cancer history. Results: The US population met the Healthy People 2010 goal for colorectal screening, but declined in all other recommended cancer screening. Cancer survivors met and maintained the HP2010 goal for all, except cervical cancer screening. Survivors had higher screening rates than the general population. Among survivors, white-collar and service occupations had higher screening rates than blue-collar survivors. Conclusions: Cancer survivors report higher screening rates than the general population. Nevertheless, national screening rates are lower than desired, and disparities exist by cancer history and occupation. Understanding existing disparities, and the impact of cancer screening on survivors is crucial as the number of working survivors increases.